2014
DOI: 10.3233/cbm-140413
|View full text |Cite
|
Sign up to set email alerts
|

Survey of autoantibody responses against tumor-associated antigens in thyroid cancer

Abstract: Although six TAAs, including one CTA, showed thyroid cancer-associated reactivity, overall, spontaneous humoral immune responses against TAAs are rare in thyroid cancer and their utility for the development of non-invasive assay for the differential diagnosis of thyroid nodules is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Among them were several previously known cancer antigens as well as novel peptides. CTAG1B, BRCA2, and SPAG8 have been previously shown to induce humoral immune response in BC ( 27 29 ) and other cancer patients ( 25 , 27 , 30 ), ANKRD30BL and COPS4 were previously found to elicit autoantibody response in gastric and thyroid cancer and melanoma ( 24 , 26 ). Artificial peptides AP1292, AP1775 and AP1361 were reacting with sera from gastric cancer patients in our previous studies ( 24 ) and may represent neoantigens or mimotopes of other cancer-associated antigens.…”
Section: Resultsmentioning
confidence: 99%
“…Among them were several previously known cancer antigens as well as novel peptides. CTAG1B, BRCA2, and SPAG8 have been previously shown to induce humoral immune response in BC ( 27 29 ) and other cancer patients ( 25 , 27 , 30 ), ANKRD30BL and COPS4 were previously found to elicit autoantibody response in gastric and thyroid cancer and melanoma ( 24 , 26 ). Artificial peptides AP1292, AP1775 and AP1361 were reacting with sera from gastric cancer patients in our previous studies ( 24 ) and may represent neoantigens or mimotopes of other cancer-associated antigens.…”
Section: Resultsmentioning
confidence: 99%
“…However, autoantigenic repertoires of many human neoplasms, eg, endocrine tumors, have not been studied in sufficient detail. Only two top-down studies identified several antigens eliciting autoantibody responses in anaplastic (25) and papillary (26) thyroid carcinomas, and few additional antigens were implicated in thyroid carcinomas in bottom-up setting (15,(27)(28)(29)(30). Importantly, none of these studies focused on encapsulated follicular-patterned lesions.…”
Section: Discussionmentioning
confidence: 90%
“…Apart from TAAs identified in a few top-down studies carried out at a whole-transcriptome/proteome-level, several additional TAAs were also implicated in thyroid neoplasia either in bottom-up or in a «semi bottom-up» (i.e., selection of TAA candidates from a set of pre-selected protein features) settings. In such a way, Abols et al [ 140 ] used a low-density phage-displayed TAA microarray comprising 65 candidate TAA features in order to test their serological reactivity in 53 patients with various thyroid carcinomas, 90 FTA patients, and 96 cancer-free individuals. Although the differences in frequencies of the cognate TAA-AAbs’ reactivity between studied groups reached statistical significance for only a single TAA (i.e., cancer-testis antigen GAGE1, Figure 2 ), the optimal cut-off values of combined serum score calculated for a six-antigen TAA panel preferentially reacted with thyroid cancer sera (i.e., GAGE1, COP9 signalosome complex subunit 4 (COPS4) and four artificial peptides most likely encoding the mimotopes of unknown antigens) discriminated the combined thyroid cancer group from FTA and healthy individuals with DSp of 97% and 90%, respectively, and DSn of 25% in both comparisons.…”
Section: The Tumor-associated Antigens (Taas) and Their Cognate Autoa...mentioning
confidence: 99%